Evaluation of the consistency of neonatal skin injury assessment using clinical images and the metric and graduated colour tool. Issue 3 (August 2022) - August, Deanne; Kandasamy, Yoga; Ray, Robin; New, Karen; Lindsay, Daniel
Abstract: Aim: To evaluate consistency in the assessment of neonatal skin injuries. Materials and methods: Injury images collected during a multicentre period prevalence study (n = 297) were screened for optimal quality before 60 images, stratified for size and colour, were randomly selected for assessment by three neonatal and two adult specialists. The principal investigator's assessments were the baseline for comparison and consistency. Injury characteristics and assessments were reported as descriptive statistics. Comparison of injury assessments for colour and stage were calculated using Chi-square, with p- value of <0.05 considered significant. Results: Neonatal specialists assessed injury elements more confidently than adult specialists reporting 59–60 (98–100%) injuries visible compared to 51–53 (85–93%) respectively. Neonatal specialists attributed mechanical force to 93% of the skin injuries compared to 70% by adult specialists. Consistency of colour assessment was achieved more often with neonatal specialists (n = 50, 85%), compared to adult specialists (n = 41, 73%). Neonatal specialists' consistency for injury staging (n = 107, 60%) was higher compared to adult specialists who were uncertain (n = 8, 16%) and less consistent (n = 47, 44%). When comparing specialists as a group, consistency with baseline assessment was significantly different between neonatal and adult specialists for colour ( p < 0.010) and injury stage ( p < 0.009). Conclusion: Field of expertise (neonatal versus adult) differences were noted likely related to experience and understanding of empirical differences between neonatal and adult skin structure and maturity. These results highlight the need for specialist neonatal skin injury and wound training for clinicians involved in assessment, treatment and best practices for neonates. Highlights: Visual assessment is inconsistent for neoantal skin integrity as healthy skin colour varies in first few weeks of life. Neonatal specialists assessed injuryies more confidently compared to adult specialists with 59–60 (98–100%) injuries visible vs 51–53 (85–93%) respectively. Across specialists, assessment of neonatal skin injury was more consistent for colour than severity.